2008
DOI: 10.1002/jssc.200800018
|View full text |Cite
|
Sign up to set email alerts
|

Packing density of slurry‐packed capillaries at low aspect ratios

Abstract: The average interparticle voidage or porosity (epsilon(inter)) in cylindrical capillaries is studied in dependence on the column diameter (d(c)) to particle diameter (d(p)) ratio for 5 < d(c)/d(p) < 50. Using optimized slurry and packing solvents, high pressure and ultrasonication, 5 mum-sized porous C18-silica particles were slurry-packed into fused-silica capillaries having ids from 30 to 250 mum. Packing densities are assessed by a polystyrene standard which is size-excluded from the intraparticle pore spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 41 publications
(44 reference statements)
2
45
0
Order By: Relevance
“…The invariance of monolithic column properties for all conduit shapes and sizes confirms the excellent scaling capability of the material within the size range tested. This finding proves the absence of the “wall effect” on column porosity, which is observed for beds packed in capillaries [43]. …”
Section: Resultssupporting
confidence: 76%
“…The invariance of monolithic column properties for all conduit shapes and sizes confirms the excellent scaling capability of the material within the size range tested. This finding proves the absence of the “wall effect” on column porosity, which is observed for beds packed in capillaries [43]. …”
Section: Resultssupporting
confidence: 76%
“…Serendipitously, this configuration provides somewhat greater inter particle porosity, and hence lower backpressure as compared to columns with closely packed (dcdp > 10) core regions. 23 We observed that a pressure drop of approximately 1400 psi across this column provided for an effluent flow rate of ≈5nL/min. at room temperature.…”
Section: Resultsmentioning
confidence: 75%
“…), the column cross section is dominated by the loosely packed “wall region,” creating a more homogeneous packing structure. 19-21, 23-24 …”
Section: Introductionmentioning
confidence: 99%
“…In order to meet this requirement, the recent utilization of nano-HPLC technology (nano-LC) allows the analysis with high sensitivity on picogram level or less. However, this technique has been involved mainly for protein analysis [8,9], and no application of HPLC-Chip on the hair-drug testing has been reported. Ketamine, known as ''K'' or ''Special-K'' or ''Kit-Kat'' in Hong Kong, has been used as an anesthetic primarily in veterinary medicine and in some short-term surgical procedures in humans since its discovery in 1961.…”
Section: Introductionmentioning
confidence: 99%